Examine the Role of Short Video Platforms on Tourist’s Attitude: A Technology Acceptance Model (TAM) Approach ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2025)
Background: In spite of the fact that Short Video Platforms (SVPs) are becoming more popular in the tourism industry, however scarce literature on SVP influence tourists’ attitude towards various SVPs is available. This study has used Technology Acceptance Model (TAM) to comprehend the tourist’s attitude towards SVPs. Objectives: The study objectives were twofold: First, to explore factors influencing tourist’s attitude towards SVP’s. Second, examining the impact of antecedents on tourist’s attitude towards SVP’s. Methodology: Exploratory research design was used in this study on 331 samples in Varanasi with a sample size of 331, purposive sampling technique was incorporated. Exploratory Factor Analysis (EFA) and multiple regressions were used to identify the factors and their relative strengths towards tourists’ attitude with respect to short video platforms (SVPs). SPSS software was used in analysing data. Results: Findings of the study revealed that perceived enjoyment is the strongest predictor of tourist’s attitude towards SVPs and perceived usefulness is the weakest one. The results suggested coefficient of determination (R2) of 0.422 that 42.20% of the variance in the dependent variable (Tourists Attitude towards Short Video Platforms) can be accounted for by the independent variables, namely perceived usefulness, perceived ease of use and perceived pleasure. Conclusion: The use of Social Media Influencers (SMIs) who demonstrate competence and the presentation of films that are both fun and user-friendly on SVPs should be the primary emphasis of Destination Marketing Organizations (DMOs) and tourist marketers for the promotion of their respective destinations.
Keywords: Social media influencers; SVP; tourist’s attitude towards SVPs; destination choice